2020
DOI: 10.2147/idr.s238559
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Rates of Antimicrobial Resistance and Virulence Gene Distribution Among<em> Shigella</em> spp. Isolated from Pediatric Patients in Tehran, Iran</p>

Abstract: Background: Shigella continues to be important causes of acute pediatric diarrhea worldwide. Shigella produces numerous virulence factors involved in colonization and invasion into epithelial cells which eventually result in the disease. The present study was conducted to evaluate the prevalence of virulence genes and to investigate antibiotic resistance profiles among Shigella isolates obtained from pediatric patients in Iran. Methods: A total of 141 Shigella isolates were collected between March 2017 and Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
3
16
1
Order By: Relevance
“…Of these, 70% belonged to the S.sonnei, 28.9% belonged to the S. flexneri and 1.1% belonged to the S. boydii (21). In 2020, Karimi-Yazdi et al (22), reported a prevalence of S. sonnei of 78.7%, S. flexneri of 19.9%, and S. boydii of 1.4%. Abbasi et al (16), examined multidrugresistant Shigella infection in children with diarrhea, out of 19 positive Shigella specimens, 21% belonged to flexneri species and 78.9% belonged to sonnei species.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 70% belonged to the S.sonnei, 28.9% belonged to the S. flexneri and 1.1% belonged to the S. boydii (21). In 2020, Karimi-Yazdi et al (22), reported a prevalence of S. sonnei of 78.7%, S. flexneri of 19.9%, and S. boydii of 1.4%. Abbasi et al (16), examined multidrugresistant Shigella infection in children with diarrhea, out of 19 positive Shigella specimens, 21% belonged to flexneri species and 78.9% belonged to sonnei species.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and antibioticresistant patterns of Shigella species are changing rapidly over time. So, antibiotic treatments are typically suggested to decrease the symptoms of Shigella infections (6)(7)(8)(9). Selecting an appropriate antibiotic for the treatment of Shigella infections is necessary because multidrug resistance (MDR) species can appear from many mechanisms, such as a decrease in cellular permeability, extrusion of drugs by active efflux pumps, and overexpression of drugmodifying in Shigella genomes (10)(11)(12)(13).…”
Section: Contextmentioning
confidence: 99%
“…In our study, all the isolates harbored ipaH , which was consistent with previous reports. 27 Most of the Shigella isolates in this study harbored ipaA, ipaB, ipaC , and ipaD , genes that regulate the secretion and translocation of several effector proteins and play a key role in intracellular actin polymerization and depolymerization. 28 The ial gene was reported to be responsible for Shigella epithelial cell penetration and cell-to-cell dissemination.…”
Section: Discussionmentioning
confidence: 90%